Pengaruh Karateristik Individu, Kompensasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan SPPBE PT. Win Med Indonesia di Sidoarjo: The Influence of Individual Characteristics, Compensation and Work Environment on Job Satisfaction of SPPBE PT. Win Med Indonesia in Sidoarjo - Meiliza, Dewi Ratiwi; Febriansah, Rizky Eka; Wahyuningtyas, Tria (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2018)
This study aims to determine the effect of individual characteristics, compensation and work environment on employee job satisfaction both partially and simultaneously. This study uses a quantitative approach. Using the technique of collecting data through questionnaires distributed to employees of PT WIN MED INDONESIA. Based on the results of the analysis, it shows that individual characteristics, compensation and work environment have a partial and simultaneous effect on employee job satisfaction. The variables that have the most significanteffect on employee job satisfaction are the work environment.